RILPIVIRIN -- nový nenukleosidový inhibitor reverzní transkriptázy HIV-1 - Snopková, Svatava; Havlíčková, Kateřina; Polák, Pavel; Šlesinger, Pavel; Husa, Petr (Klinicka mikrobiologie a infekcni lekarstvi, 2013)
The article summarizes the basic facts about the pharmacokinetic profile, metabolism and drug interactions of rilpivirine (RPV). This is the latest orally administered second-generation non-nucleoside reverse transcriptase inhibitor (NNRTI) for antiretroviral-naive patients with HIV-1 infection. Conformational flexibility and adaptability are the factors that dominantly determine the high resistance barrier of RPV and are the unique features of diarylpyrimidine inhibitors (DAPY inhibitors - 2nd generation NNRTIs). Multicentre studies ECHO and THRIVE are also reviewed. Current guidelines for the treatment of HIV/AIDS are mentioned as well as the role of RPV in current therapeutic regimens.
Keywords: HIV Infections; HIV reverzní transkriptasa; rilpivirin; nitrily; Rilpivirine; Humans; Pyrimidines; lidé; HIV-1; pyrimidiny; Nitriles; HIV infekce; HIV Reverse Transcriptase